Efficacy of a tight-control and treat-to-target strategy in axial spondyloarthritis: results of the open-label, pragmatic, cluster-randomised TICOSPA trial. Issue 11 (6th May 2021) - Molto, Anna; López-Medina, Clementina; Van den Bosch, Filip E; Boonen, Annelies; Webers, Casper; Dernis, Emanuelle; van Gaalen, Floris A; Soubrier, Martin; Claudepierre, Pascal; Baillet, Athan; Starmans-Kool, Mirian; Spoorenberg, Anneke; et al.
Abstract : Objectives: To compare the benefits of a tight-control/treat-to-target strategy (TC/T2T) in axial spondyloarthritis (axSpA) with those of usual care (UC). Methods: Pragmatic, prospective, cluster-randomised, controlled, open, 1-year trial (NCT03043846 ). 18 centres were randomised (1:1). Patients met Axial Spondylo Arthritis International Society (ASAS) criteria for axSpA, had an Ankylosing Spondylitis Disease Activity Score (ASDAS) ≥2.1, received non-optimal treatment by non-steroidal anti-inflammatory drugs and were biologic-naive. Interventions: (1) TC/T2T : visits every 4 weeks and prespecified strategy based on treatment intensification until achieving target (ie, ASDAS <2.1); (2) UC: visits every 12 weeks and treatment at the rheumatologist's discretion. Main outcome: Percentage of patients with a ≥30% improvement on the ASAS-Health Index (ASAS-HI). Other efficacy outcomes and adverse events were recorded. A health economic evaluation was performed. Statistical analysis: Two-level mixed models were used to estimate efficacy outcomes. Cost-effectiveness was assessed by the incremental cost per quality-adjusted life-year (QALY) gained for TC/T2T versus UC. Results: 160 patients were included (80/group). Mean (SD) age was 37.9 (11.0) years and disease duration was 3.7 (6.2) years; 51.2% were men. ASDAS at inclusion was 3.0 (0.7), and ASAS-HI was 8.6 (3.7). ASAS-HI improved by ≥30% in 47.3% of the TC/T2T arm and in 36.1% of those receiving UC (non-significant). All secondary efficacy outcomes were more frequent in the TC/T2T arm, although not all statistically significant. Safety was similar in both arms. From a societal perspective, TC/T2T resulted in an additional 0.04 QALY, and saved €472 compared with UC. Conclusion: TC/T2T was not significantly superior to UC for the primary outcome, while many secondary efficacy outcomes favoured it, had a similar safety profile and was favourable from a societal health economic perspective. Trial registration number: NCT03043846 .